Evaluación del rendimiento de híbridos simples y triples de maíz amarillo duro en el cantón Bolívar, Manabí - Carrión Vélez, Andrés David (2025)
The objective of the study was to evaluate the performance of single and triple yellow dent maize hybrids in Bolívar Canton, Manabí. The research was experimental, qualitative, and quantitative, using yellow dent maize as the crop. The treatments studied were: PORT.PHAEO.1AS2. 4-1-1-1 X CLYN-352, LP3a X CML-362, LP3A X CLYN-560, CML-437 X L.I.4, PORT.PHAEO.1AS2. 4-1-1-1 X CLYN-485, (G1.2. 18-2-1-1 X CML-451) X CML-3, (G1.2. 18-2-1-1 X CML-451) X CML-437, (G1.2. 18-2-1-1 X CML-451) X CLYN-48, (G1.2. 18-2-1-1 X CML-451) X L.I.4, (LP3a X P79.RH. 133-1-2) X G-I-2. 18-2-1-1, INIAP 601, INIAP 603, ESPLENDOR, TRUENO, and ADV 9559. Among the 15 experimental and commercial yellow dent maize hybrids, the commercial hybrids performed better in agronomic components and in the grain percentage variable, with the commercial hybrid TRUENO achieving an average grain percentage of 86.7%. The experimental hybrids outperformed the commercial ones in traits such as plant height, reaching 3003.33 cm (PORT.PHAEO.1AS2. 4-1-1-1 X CLYN-352), and ear insertion height, reaching 139 cm (CML-437 X L.I.4).